Being an 'agent provocateur': utilising online spaces for teacher professional development in virtual simulation games. Issue 3 (26th May 2016) - deNoyelles, Aimee; Raider-Roth, Miriam
Abstract : This article details the results of an action research study which investigated how teachers used online learning community spaces to develop and support their teaching and learning of the Jewish Court of All Time (JCAT), a web-mediated, character-playing, simulation game that engages participants with social, historical and cultural curricula. The nature of reflection that was generated in the asynchronous and synchronous professional development spaces is discussed. Data analysis of online discussion and chat transcripts revealed that two forms of reflection were generated: reflection on self-as-teacher (juggling roles, responsibility, teaching challenges) and reflection on students (socio-cognitive and relational dimensions). The results speak to the importance of selecting online spaces that support the overall objectives of the professional development, as well as provide a rich forum to discuss the game in question. Having both asynchronous and synchronous spaces allows teachers the freedom to express themselves in multiple ways. Findings guide instructional design, generate insight on the interaction of online spaces and support teachers in how they learn and teach virtual simulation game experiences.